The wound's future. Issue 1 (March 2020) - Rice, Jenny
While we so commonly frame our public/civic wounds as past (or passed), we are used to talking about healing and mending existing wounds. This language also affects how we conduct deliberative discourse around current crises. However, I am more curious about the wound's future. Specifically, I want to explore the wound's future as it emerges in two different types of deliberation: prescriptive deliberation and descriptive deliberation. Rather than seeing the wound (only) as something that has already happened, or even as something that lingers on into the present, I want to address the wound's future: a tactical future-oriented rhetoric that creates a broader deliberative practice.